Synthesis of Tetraazamacrocyclic Crown Ether Ni(II) Complex and Electrochemical Study of its Interaction with DNA - Bi, Jian-Hong; Chen, Yan (Asian Journal of Chemistry, 2011)
A tetrazamacrocyclic crown ether complex of Ni(II) with the composition [NiL](ClO4)2 (L = 5,12-dimethyl-7,14-diphenyl-1,4,8,11-tetraazamacrocyclotetradecane) was synthesized and characterized by IR spectra and elemental analysis. The mutual effects of the [NiL](ClO4)2 with DNA were studied by electrochemical method. In the presence of DNA, the redox peaks of [NiL](ClO4)2 shifted to more positive values and the peak current increased greatly. The experimental results demonstrate that the [NiL](ClO4)2 could interact with DNA by intercalation binding mode.